A qualitative examination of football players` acceptability and perceptions on the use of virtual reality in football training - Shields, A. U.; Neumann, D. L.; Stainer, M. J. (PLOS ONE, 2025)
Introduction Virtual reality (VR) technologies are being increasingly used for training among football teams. Despite this, limited research has examined football players` acceptability and perceptions of VR training. It is essential to understand football players` perspectives on this training approach to identify any psychological factors that may influence its uptake.